North American Propolis Extracts From Upstate New York Decrease Nosema ceranae (Microsporidia) Spore Levels in Honey Bees (Apis mellifera) - Burnham, Andre J.; De Jong, Emily; Jones, Jayre A.; Lehman, Herman K. (Frontiers in Microbiology, 2020)
Nosema ceranae infections in honey bees (Apis mellifera) pose a severe threat to colony health. Beekeepers have used dicyclohexylammonium fumagillin to control Nosema apis, although it may be ineffective against N. ceranae. We investigated the ability of various propolis extracts collected from Upstate New York (U.S.A) to decrease in vivo N. ceranae infection levels when fed ad libitum to N. ceranae-infected honey bees. Propolis extracts, most notably a dichloromethane extract, significantly lowered spore levels in a dose-dependent fashion four days post inoculation. When testing the in vitro anti-Nosema activity of propolis extracts, we report for the first time that spore viability was unaffected after a 24 hr exposure to propolis extracts. These results present evidence that propolis extracts may effectively lower Microsporidia infections in honey bees, and that direct exposure of environmental spores to propolis alone does not kill N. ceranae.